2010
DOI: 10.1097/eja.0b013e32832d6a76
|View full text |Cite
|
Sign up to set email alerts
|

Automated reminders increase adherence to guidelines for administration of prophylaxis for postoperative nausea and vomiting

Abstract: Decision support is effective in improving administration and timing of PONV prophylaxis medication. After withdrawal of decision support, adherence decreased to predecision support levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 15 publications
0
29
0
1
Order By: Relevance
“…In a similar vein, Kooij found that in the preoperative setting, CDS could increase adherence to prescribing PONV prophylactic treatment in high‐risk PONV patients from 38% to 73% 58. A follow‐up study has demonstrated that automated reminders could increase adherence to guidelines for the actual administration of PONV prophylaxis 59. Gawande, the World Health Organization and others have done a significant amount of work establishing the importance and value of a Surgical Safety Checklist, otherwise known as a “pre‐incision timeout,” to avoid preventable surgical adverse events that have been found to be preventable 54% of cases 60.…”
Section: Current Usage Of Decision Support In Practice Of Anesthesiamentioning
confidence: 88%
“…In a similar vein, Kooij found that in the preoperative setting, CDS could increase adherence to prescribing PONV prophylactic treatment in high‐risk PONV patients from 38% to 73% 58. A follow‐up study has demonstrated that automated reminders could increase adherence to guidelines for the actual administration of PONV prophylaxis 59. Gawande, the World Health Organization and others have done a significant amount of work establishing the importance and value of a Surgical Safety Checklist, otherwise known as a “pre‐incision timeout,” to avoid preventable surgical adverse events that have been found to be preventable 54% of cases 60.…”
Section: Current Usage Of Decision Support In Practice Of Anesthesiamentioning
confidence: 88%
“…In this study, the researchers compared prophylactic antiemetic prescription rates after the reminder was implemented and discovered a 38% pre‐intervention increase in prophylaxis. After the reminder was discontinued, there was a decrease of 41% in prescribing prophylactic antiemetics 10 . As a follow‐up, Kooij et al 10 re‐implemented the guidelines; in the pre‐admission testing phase of care, when patients were determined to need intraoperative PONV prophylaxis, adherence to prescribing guidelines increased from 37% to 79%.…”
Section: Guideline Description and Rationalementioning
confidence: 99%
“…After the reminder was discontinued, there was a decrease of 41% in prescribing prophylactic antiemetics 10 . As a follow‐up, Kooij et al 10 re‐implemented the guidelines; in the pre‐admission testing phase of care, when patients were determined to need intraoperative PONV prophylaxis, adherence to prescribing guidelines increased from 37% to 79%. This research supports the integration of individualized clinical decision support tools into electronic systems as a reminder for perioperative staff members to order antiemetic medications based on the patient's level of risk.…”
Section: Guideline Description and Rationalementioning
confidence: 99%
“…Daher ist eine großzügigere generelle Prophylaxe zu überdenken, die dann noch einmal bei besonders gefährdeten Patienten (z. B. Kieferverdrahtung) ausgedehnt werden könnte, um ein noch wirksameres Regime zur Anwendung zu bringen [14,15].…”
Section: Statistische Analyseunclassified